Makers of democracy : a transnational history of the middle classes in Colombia - López, A. Ricardo, 1974- (Radical perspectives., 2019)
A. Ricardo López-Pedreros traces the ways in which a thriving middle class was understood to be a foundational marker of democracy in Colombia in the second half of the twentieth century, showing democracy to be a historically unstable and contentious practice.